Treatment with the anti-IgE monoclonal antibody omalizumab in women with asthma undergoing fertility treatment: a proof-of-concept study—The PRO-ART study protocol - Karsten Kristiansen; Nina La Cour Freiesleben; Charlotte Suppli Ulrik; Henriette Svarre Nielsen; Casper Tidemandsen; Elisabeth Juul Gade; Birgitte Sophie Oxlund-Mariegaard; Bugge Nøhr; Hanne Udengaard; Vibeke Backer (BMJ Open, 2020)
Introduction Asthma is associated with prolonged time to pregnancy and a higher need for fertility treatment. However, the mechanism underlying this association remains incompletely understood. Previous research points to asthma-driven systemic inflammation also affecting the reproductive organs and thereby fertility. The aim of this study was to determine if treatment with omalizumab prior to fertility treatment will increase pregnancy rate among women with asthma by decreasing the systemic asthma-related inflammation and, by that, to provide insight into the underlying mechanisms.Methods and analysis This is an ongoing prospective multicentre randomised controlled trial planned to enrol 180 women with asthma recruited from fertility clinics in Denmark. The patients are randomised 1:1 to either omalizumab or placebo. The primary endpoint is the difference in pregnancy rate confirmed with ultrasound at gestational week 7 of pregnancy. The secondary endpoints are change in sputum and blood eosinophil cell count, change in biomarkers, change in microbiota, together with rate of pregnancy loss, frequency of malformations, pre-eclampsia, preterm birth, birth weight, small for gestational age and perinatal death between groups.Ethics and dissemination The methods used in this study are of low risk, but if successful, our findings will have a large impact on a large group of patients as infertility and asthma are the most common chronic diseases among the young population. The study has been approved by the Ethics Committee–Danish national research ethics committee (H-18016605) and the Danish Medicines Agency (EudraCT no: 2018-001137-41) and the Danish Data Protection Agency (journal number: VD-2018486 and I-Suite number 6745). The test results will be published regardless of whether they are positive, negative or inconclusive. Publication in international peer-reviewed scientific journals is planned.Trial registration number NCT03727971.